Migration in an 'Age of Uncertainty' : the creation of a Polish community in the Vaal Triangle, South Africa (1980-1989) - Macqueen, Ian (University of Pretoria, 2023)
Dissertation (MSocSci (History))--University of Pretoria, 2023.